2015
DOI: 10.1007/s10886-015-0601-y
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground and Belowground Herbivores Synergistically Induce Volatile Organic Sulfur Compound Emissions from Shoots but Not from Roots

Abstract: Studies on aboveground (AG) plant organs have shown that volatile organic compound (VOC) emissions differ between simultaneous attack by herbivores and single herbivore attack. There is growing evidence that interactive effects of simultaneous herbivory also occur across the root-shoot interface. In our study, Brassica rapa roots were infested with root fly larvae (Delia radicum) and the shoots infested with Pieris brassicae, either singly or simultaneously, to study these root-shoot interactions. As an analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…Semiochemicals that function in these interactions can be produced constitutively or in response to outside interactions and stimuli, and this occurs above as well as below ground (Massalha et al ., ). Although there are indications that above‐ and below‐ground semiochemical responses are integrated (Danner et al ., ; Van Dam et al ., ), details on what drives this remain to be elucidated. Although semiochemicals can travel long distances, plant−plant and plant−microbe communication usually take place at relatively short distances, while plant volatiles with a role in plant−insect interaction are perceived at distances of several hundred metres.…”
Section: Analysis and Information Content Of Vocsmentioning
confidence: 99%
“…Semiochemicals that function in these interactions can be produced constitutively or in response to outside interactions and stimuli, and this occurs above as well as below ground (Massalha et al ., ). Although there are indications that above‐ and below‐ground semiochemical responses are integrated (Danner et al ., ; Van Dam et al ., ), details on what drives this remain to be elucidated. Although semiochemicals can travel long distances, plant−plant and plant−microbe communication usually take place at relatively short distances, while plant volatiles with a role in plant−insect interaction are perceived at distances of several hundred metres.…”
Section: Analysis and Information Content Of Vocsmentioning
confidence: 99%
“…Depending on the plant species studied, volatile blends released belowground by plant roots can be characterized by compounds belonging to various chemical families, particularly terpenoids (Rasmann et al 2005;Lin et al 2007;Ali et al 2010), fatty acid derivatives (Gfeller et al 2013) or sulphur-containing compounds (Ferry et al 2007;Crespo et al 2012;Danner et al 2015). Important ecological roles have been associated with root-emitted VOCs (Fig.…”
Section: Plant Roots Release Vocs Involved In Belowground Biotic Intementioning
confidence: 99%
“…GC-MS and proton transfer reaction-mass spectrometry (PTR-MS) analyses have shown that insect-damaged Brassica roots release mainly highly volatile sulphur compounds (methanethiol, dimethyl sulphide, dimethyl disulphide and dimethyl trisulphide) and glucosinolate breakdown products (thiocyanates and isothiocyanates) in the soil, with a VOC emission pattern depending on the plant species studied Danner et al 2012;Crespo et al 2012;Danner et al 2015). To date, PTR-MS analyses of root-emitted VOCs have been performed only on potted Brassica spp.…”
Section: Td-gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, there is experimental evidence that the concurrent feeding by aboveground feeding nonhosts does not affect parasitization levels of suitable herbivores in long-term experiments (Chabaane et al, 2015;de Rijk et al, 2016). Root herbivore feeding, however, causes shifts in Brassica HIPV profiles which reduce parasitization rates both in the field and in spatially explicit experiments (Soler et al, 2007a,b;Pierre et al, 2011;Danner et al, 2015). It was postulated that these parasitoids avoid plants with root herbivores because their offspring's performance will be reduced as a result of changes in the plant's metabolome that are trickling up via their herbivorous hosts (Soler et al, 2005;Qiu et al, 2009).…”
Section: Researchmentioning
confidence: 99%